Evil friends: childhood friendship and diasporic identities in Meera Syal’s Anita and me and Helen Oyeyemi’s The Icarus Girl (Philologia, 2021)
Childhood fiction has received great critical attention due to its exploration of identity development, a tendency which can also be observed in contemporary diasporic narratives dealing with the experience of ethnic minority children. Two of such narratives are Anita and Me (1996) by Indian-British Meera Syal and The Icarus Girl (2005) by Nigerian-British Helen Oyeyemi, both focused on the childhood experiences of two girls from ethnic minorities who grow up in racist societies. This essay surveys the connections that can be observed between both novels as they deploy the friendship motif in their depiction of the protagonists’ identity conflicts after turning to damaging friendships for identification and approval. The assessment of the links between both narratives leads to insightful reflections regarding diasporic writing and identity formation in migrant children.
Keywords: identity; diasporic fiction; childhood narratives; friendship; ethnicity; Meera Syal; Helen Oyeyemi